Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.energy.2010.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing a self-managed CHP system for greenhouse cultivation as a profitable way to reduce CO2-emissions

Abstract: a b s t r a c tTo counter global warming, a transition to a low-carbon economy is needed. The greenhouse sector can contribute by installing Combined Heat and Power (CHP) systems, known for their excellent energy efficiency. Due to the recent European liberalization of the energy market, glass horticulturists have the opportunity to sell excess electricity to the market and by tailored policy and support measures, regional governments can fill the lack of technical and economic knowledge, causing initial resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 16 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…This makes all actions that minimize the environmental impacts related to food production important [1]. As the greenhouse sector is among the more energy-consuming sectors within agriculture [2], it is of interest to study the environmental impacts of greenhouse grown vegetables and to investigate possible improvements. In this study life cycle assessment (LCA) is used to evaluate the environmental performance of producing tomatoes in Norwegian (Sør-Trøndelag) greenhouses heated with a micro-scale bio-fuelled gasification CHP and this system will be compared to conventional open-field tomatoes grown and shipped from southern Europe (Mediterranean Spain) to Northern Scandinavia (Trondheim, Norway).…”
Section: Introductionmentioning
confidence: 99%
“…This makes all actions that minimize the environmental impacts related to food production important [1]. As the greenhouse sector is among the more energy-consuming sectors within agriculture [2], it is of interest to study the environmental impacts of greenhouse grown vegetables and to investigate possible improvements. In this study life cycle assessment (LCA) is used to evaluate the environmental performance of producing tomatoes in Norwegian (Sør-Trøndelag) greenhouses heated with a micro-scale bio-fuelled gasification CHP and this system will be compared to conventional open-field tomatoes grown and shipped from southern Europe (Mediterranean Spain) to Northern Scandinavia (Trondheim, Norway).…”
Section: Introductionmentioning
confidence: 99%
“…The development of cogeneration plants of various types is a relevant task, because it allows improvement in efficiency and provides implementation of additional functions. Typical solution is a combination of the mini-CHP with greenhouses [10], but this solution largely restricts the scope of application of the plants. More effective is to design plants that would make it possible, along with electric and thermal energy, to produce additional much-needed products.…”
Section: Discussion Of Results Of Development Of the Automated Systemmentioning
confidence: 99%
“…One of the solutions to reduce carbon emissions, proposed both in article [10] and by the manufacturers of mini-CHP, is a combination of mini-CHP with a greenhouse, which is both a consumer of heat and a consumer of carbon dioxide, received by smoke purification. This approach, however, dramatically narrows the scope of mini-CHP application.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…These topics have often been discussed in technical literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Feng et al [1] proposed a new performance index for cogeneration systems that takes into account the effect of "anergy" in heating, and compared it with four well-known criteria: energy utilization factor, artificial thermal efficiency, fuel energy saving ratio and exergy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Compernolle et al [14] have analysed a CHP system for greenhouse cultivation using the net present value approach and the local and global scale balance for CO 2 , CO and NO x . The authors concluded that CHP can be a cost effective technology for greenhouse cultivation and can help to reach emission reduction targets.…”
Section: Introductionmentioning
confidence: 99%